2022
DOI: 10.3389/fpsyt.2022.800290
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity Relates to Multi-Trial Choice Strategy in Probabilistic Reversal Learning

Abstract: Impulsivity is defined as a trait-like tendency to engage in rash actions that are poorly thought out or expressed in an untimely manner. Previous research has found that impulsivity relates to deficits in decision making, in particular when it necessitates executive control or reward outcomes. Reinforcement learning (RL) relies on the ability to integrate reward or punishment outcomes to make good decisions, and has recently been shown to often recruit executive function; as such, it is unsurprising that impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…• 3-back feedback integration: The 3-back analysis quantifies learning as well; however, instead of aligning the performance to reversal points, it allowed us to examine agents' tendency to repeat action selection from the previous trial contingent on reward history-specifically the outcome they observed on the most recent 3 trials. Higher probability of repeating the same action following more positive feedback indicates learning/sensitivity to reward as reported in [11] • Ab-analysis: The Ab-analysis allowed us to quantify probability of selecting an action at trial t,contingent both on previous reward and action selection history (trials t − 2 and t − 1, [11,80]).…”
Section: Likelihood-dependent Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• 3-back feedback integration: The 3-back analysis quantifies learning as well; however, instead of aligning the performance to reversal points, it allowed us to examine agents' tendency to repeat action selection from the previous trial contingent on reward history-specifically the outcome they observed on the most recent 3 trials. Higher probability of repeating the same action following more positive feedback indicates learning/sensitivity to reward as reported in [11] • Ab-analysis: The Ab-analysis allowed us to quantify probability of selecting an action at trial t,contingent both on previous reward and action selection history (trials t − 2 and t − 1, [11,80]).…”
Section: Likelihood-dependent Methodsmentioning
confidence: 99%
“…Furthermore, by estimating model parameters that quantify underlying cognitive processes, researchers have been able to characterize important individual differences (e.g. developmental: [7][8][9][10]; clinical: [11][12][13][14][15]) as well as condition effects [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This summary statistic should capture learning dynamics, as the agent learns to select the correct action, and then experiences dip in accuracy once the correct actions switch, subsequently learning to adjust based on feedback after several trials. 3-back feedback integration: The 3-back analysis quantifies learning as well; however, instead of aligning the performance to reversal points, it allowed us to examine agents’ tendency to repeat action selection from the previous trial contingent on reward history - specifically the outcome they observed on the most recent 3 trials. Higher probability of repeating the same action following more positive feedback indicates learning/sensitivity to reward as reported in Zou et al, 2022 Ab-analysis: The Ab-analysis allowed us to quantify probability of selecting an action at trial t ,contingent both on previous reward and action selection history (trials t − 2 and t − 1, Beron et al, 2021; Zou et al, 2022). For the models simulated on a hierarchical task we used the learning curves as summary statistics (same as for the PRL), where reversal points were defined as the switch of the correct rule/arrow to follow.…”
Section: Methodsmentioning
confidence: 99%
“…Higher probability of repeating the same action following more positive feedback indicates learning/sensitivity to reward as reported in Zou et al, 2022 • Ab-analysis: The Ab-analysis allowed us to quantify probability of selecting an action at trial t,contingent both on previous reward and action selection history (trials t − 2 and t − 1, Beron et al, 2021;Zou et al, 2022).…”
Section: Likelihood Approximation Methodsmentioning
confidence: 99%
See 1 more Smart Citation